Nationalising the crusades - Horswell, Mike (Engaging the crusades, 2023)
Introduction: Crusade and nation / Mike Horswell -- "Heroes and martyrs"?: national memories and foreign crusaders in Portuguese commemorations of the eighth centenary of the conquest of Lisbon (1947) / Pedro Martins -- The Tsar's crusade: invented holy war tradition in Russia (1780-1920) / Adam Knobler -- Perceptions of crusader 'Athlit in Zionist writing (1887-1941) / Judith Bronstein -- Cultural brokers in the nationalisation of crusader architecture / Astrid Swenson -- Bushido, chivalry and the crusades in Japan from the 1870s to the First World War / Oleg Benesch.